The Forms of Loanwords in Sports News in the Online Newspaper Rakyat Bengkulu - Febianto, Febianto; Yumarni , Asmara; Sari , Wenny Aulia (The Future of Education Journal, 2025)
This study aims to examine the forms of loanwords in sports news in the online newspaper Rakyat Bengkulu. The research uses a qualitative approach, focusing on exploring processes, events, and developments in language use. Data were collected from Rakyat Bengkulu online during June, July, and August 2022. The study finds that loanwords in the sports news are primarily derived from English. For example, the word "sportivitas" (sportiveness) is a loanword from the English "sportivity," which has been adapted into Indonesian. Loanword adaptations in the sports news include both direct borrowing without changes in form or meaning, such as the word "Event," which is borrowed directly from English, meaning "occurrence," "event," or "occasion." Additionally, there are adaptations of foreign words with modifications to fit the recipient language, as seen in the use of "E-Sport," which has become a global phenomenon with numerous online and offline tournaments and competitions.